Molecular Fe-complex as a catalyst probe for in-gel visual detection of proteins via signal amplification - Kumari, Sushma; Panda, Chakadola; Mazumdar, Shyamalava; Sen Gupta, Sayam (Chemical Communications, 2015)
We report the use of a molecular peroxidase mimic biuret-Fe-TAML for chemoselective labeling of proteins and the subsequent visual detection (<0.1 pmoles) of the conjugate in a polyacrylamide gel by catalytic signal amplification. Use of this probe in activity based protein profiling (ABPP) of serine proteases is also demonstrated.